2019
DOI: 10.2503/hortj.utd-047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maturation Stage and Storage Temperature and Duration on β-Cryptoxanthin Content in Satsuma Mandarin (<i>Citrus unshiu</i> Marc.) Fruit

Abstract: In satsuma mandarin fruit (Citrus unshiu Marc.), β-cryptoxanthin is a major carotenoid and an important quality component in the juice sacs. The stage of maturity and storage conditions of satsuma mandarin fruit shipped to markets varies. However, the effects of maturation stage, storage temperature and duration on changes in β-cryptoxanthin content have not been fully studied. In the present study, fruits were harvested at different maturation stages, and changes in β-cryptoxanthin content in the juice sacs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The dynamic quality of PRAP is jointly influenced by picking maturity, preservation temperature, and storage time (e.g., Matsumoto et al., 2019; Singh et al., 2019; Ribeiro and de Freitas, 2020). In production practice, PRAP maturity is divided into several stages.…”
Section: Model Formulationmentioning
confidence: 99%
“…The dynamic quality of PRAP is jointly influenced by picking maturity, preservation temperature, and storage time (e.g., Matsumoto et al., 2019; Singh et al., 2019; Ribeiro and de Freitas, 2020). In production practice, PRAP maturity is divided into several stages.…”
Section: Model Formulationmentioning
confidence: 99%
“…Low-temperature storage at a suitable temperature is beneficial for maintaining the appearance, colour and exterior quality of fruits, improving the storability, and prolonging the shelf life (Hong et al, 2013;Lado et al, 2018;Matsumoto et al, 2019). To some extent, the fruit colour reflects the freshness and postharvest quality of horticultural products.…”
Section: Effects Of Different Storage Temperatures On Dr Wl L* and CCImentioning
confidence: 99%
“…Cold storage is the most frequently used preservation technology to maintain postharvest quality and extend the storage life of fresh citrus fruits, such as grapefruits, mandarins, tangerines and lemons (Montero et al, 2009;Undurraga et al, 2009;Chaudhary et al, 2017;Matsumoto et al, 2019). The recommended storage temperatures (RST) for postharvest citrus fruit range from 5 °C to 8 °C (Tietel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When fruits were pretreated at 20 ℃, then duration period was shorter, fruit weight loss and the degree of decay at the later stage was less, peel color turned to deeper orange and respiration rate during storage was lower than those pretreated at 10 ℃ in Satsuma mandarin [32]. Matsumoto [33] found that the content of β-cryptoxanthin continued to increase following 15 days of storage in fruit harvested when β-cryptoxanthin was still being accumulated in 'Aoshima' Satsuma mandarin. Fruit of 'Shiranuhi' stored at 12 ℃ with MA packing showed superior rind and flesh color and eating quality.…”
Section: Storage and Physiological Disorders In Citrusmentioning
confidence: 99%